Llm як інструмент для емоційної нейтралізації тексту - Білоконь, Б. О. (ХНУРЕ, 2024)
Emotionality in communication can have both positive and negative effects, depending on how it is used and controlled. The aim of this paper is to investigate the effectiveness and accuracy of emotional neutralization of texts using LLM, while preserving semantics and main meaning. The study uses prompt engineering methods to build queries whose answers will have the best results.
Keywords: нейтралізація; спілкування; ChatGPT; LLM